PUBLIC PRACTICS IN MANAGEMENT OF A SOCIAL HEALTH CRISIS: LESSONS LEARNED FROM PANDEMIC TREATMENT OF COVID-19 - Ade Risna Sari (Adisam Publisher, 2024)
The COVID-19 pandemic has triggered an unprecedented global health crisis, forcing countries around the world to reevaluate and adjust public policy strategies. Studies in this research are literature by looking for literature in accordance with the context of research. The results of this study show that the importance of dynamic adaptation, multilateral cooperation, and sustainable investment in health resources, capacity development, and innovation are key pillars in strengthening global preparedness and response to health crises. The policy implications resulting from this study require deep reflection and strategic reorganization in public health crisis management, highlighting the requirements for a more inclusive, evidence- based, and participatory approach.